Competência em informação na era da pós-verdade: a (in)formação na graduação em biblioteconomia e ciência da informação da UFSCar - Dias, Fernando Brito da Costa (Universidade Federal de São Carlos, 2021)
The terms disinformation and fake news are used to denote false information or rumors that are mostly published on social networks, which often aim to manipulate public opinion or defame something or someone. This scenario increases in tandem with the ease of producing information on the web. Thus, the present study seeks to relate the topic of disinformation, fake news and information literacy - topics studied in Information Science - to Higher Education. Discussions about information literacy address the user's ability to recognise the need for certain information and have the necessary skills to locate, evaluate and use it in order to meet their need. This research is of a descriptive-exploratory nature as a way of identifying content related to the topic of information literacy in the curriculum of the undergraduate course in Library and Information Science at the Federal University of São Carlos and verifying whether such content contributes to reducing the sharing of disinformation and fake news by students. For the structuring of the research, a bibliographical survey of scientific publications on the subject was carried out, using the subjects ‘information literacy’, ‘post-truth’, ‘disinformation’, ‘fake news’ and ‘agnotology’. For data collection, a questionnaire was applied virtually to students in the first and fourth years of the undergraduate course. The data were analysed using a qualitative and quantitative approach in order to identify the level of information literacy of students from the questions answered based on indicator two of standard three of the Information Literacy Competency Standards for Higher Education of the Association of College and Research Libraries (ACRL), a division of the American Library Association. According to indicator two of standard three, an information literate student must be able to master and use initial methods of evaluating information and its sources. After the study, the hypothesis that there are subjects in the course that have content that relate to the development of skills related to information literacy was proven. The identified disciplines are related to the use of ICT; the recognition of how information is developed, manipulated, organised, stored, made available and disseminated; skills related to research techniques and awareness of the ethical and legal use of information. Of the 16 subjects identified, only 6 are offered in the first year of the course, which puts first year students at a disadvantage when compared to those in the fourth year. The disciplines contribute to the development of skills related to the development of information literacy by addressing content related to information literacy. In addition, after analysing the responses to the questionnaire, it was found that first year students are more likely to share misinformation on social networks, since the rate of verification of such content is lower than that of fourth year students, which reinforces the hypothesis that the curriculum of the course tangibly contributes to the development of information literate students.
Information literacy in the post-truth era: undergraduate (in)formation in librarianship and information science at UFSCar
Habilidades informativas en la era de la posverdad: pregrado (in)formación en bibliotecología y ciencias de la información en la UFSCar
Keywords: Ensino superior; Ciência da informação; Competência em informação; Desinformação; Pós-verdade; Agnotologia; Compartilhamento de conteúdo; Redes sociais; Informações falsas; Higher education; Information science; Information literacy; Disinformation; Fake news; Post-truth; Agnotology; Sharing contente; Social networks; False information; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO